The ‘galli’s’ castrated body in the curses of ‘Mogontiacum’: an analysis of five 'defixiones' for 'Magna Mater' - Silva, Semíramis Corsi (Romanitas - Revista de Estudos Grecolatinos, 2023)
The cult of Cybele, the Mater Magna of the Romans, and her consort Attis, had a great development in the first centuries of the Roman Empire. Remembering and updating a series of mythological narratives around Cybele and Attis, it was common to carry out an intervention in the body of their priests, the galli, seen as a castration that removed the masculinity of these subjects in the literature that has come down to us. From five curse tablets (defixiones) found in the Temple of Isis and Mater Magna in the German city of Mainz, the ancient Mogontiacum, I will analyze the view that the local population had in relation to the practice of ritual castration of the galli. I aim to understand elements of the popular imagination about the body of such priests and their use in magical rituals.
Keywords: Magic; Defixiones; Galli; Castrated priests; Magna Mater